Hidden riches : a sourcebook for the comparative study of the Hebrew Bible and ancient Near East - Hays, Christopher B., 1973- (Louisville Westminster John Knox press, 2014)
"This study considers the historical, cultural, and literary significance of some of the most important Ancient Near East (ANE) texts that illuminate the Hebrew Bible. Christopher B. Hays provides primary texts from the Ancient Near East with a comparison to literature of the Hebrew Bible to demonstrate how Israel's Scriptures not only draw from these ancient contexts but also reshape them in a unique way. Hays offers a brief introduction to comparative studies, then lays out examples from various literary genres that shed light on particular biblical texts. Texts about ANE law collections, treaties, theological histories, prophecies, ritual texts, oracles, prayers, hymns, laments, edicts, and instructions are compared to corresponding literature in the Pentateuch, Prophets, and Writings of the Hebrew Bible. The book includes summaries to help instructors and students identify key points for comparison. By considering the literary and historical context of other literature, students will come away with a better understanding of the historical, literary, and theological depth of the Hebrew Bible"--
Includes bibliographical references and indexes.
Keywords: Bible. -- Comparative studies; Bible. -- Criticism, interpretation, etc; Bible. -- Extra-canonical parallels; Middle Eastern literature -- Relation to the Old Testament